Stabilize and connect: the role of LARP7 in nuclear non-coding RNA metabolism - Hasler, Daniele (RNA Biol, 2020)
La and La-related proteins (LARPs) are characterized by a common RNA interaction platform termed the La module. This structural hallmark allows LARPs to pervade various aspects of RNA biology. The metazoan LARP7 protein binds to the 7SK RNA as part of a 7SK small nuclear ribonucleoprotein (7SK snRNP), which inhibits the transcriptional activity of RNA polymerase II (Pol II). Additionally, recent findings revealed unanticipated roles of LARP7 in the assembly of other RNPs, as well as in the modification, processing and cellular transport of RNA molecules. Reduced levels of functional LARP7 have been linked to cancer and Alazami syndrome, two seemingly unrelated human diseases characterized either by hyperproliferation or growth retardation. Here, we review the intricate regulatory networks centered on LARP7 and assess how malfunction of these networks may relate to the etiology of LARP7-linked diseases.